2005
DOI: 10.1039/b419305a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of quantum dot–lectin conjugates as novel fluorescent probes for microscopic and flow cytometric identification of leukemia cells from normal lymphocytes

Abstract: The present study describes a synthesis of QD-lectin conjugates and their application for identification of leukaemia cells from normal lymphocytes using fluorescent confocal microscopy and flow cytometry. The results are compared with commercially available FITC-lectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 12 publications
0
43
0
Order By: Relevance
“…To exploit the advantageous aspects of QDs, various fluorescent sensors have been developed to address their biocompatibility for biological applications. [10][11][12][13][14][15][16][17][18] A most important advantage is that the QD can be dispersed in the water by functionalizing the surface. 19,20 Simple but useful fluorescent sensors based on QDs in previous studies monitored changes in the pH through single peak emission changes that occurred by a photoinduced electron transfer (PET) mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…To exploit the advantageous aspects of QDs, various fluorescent sensors have been developed to address their biocompatibility for biological applications. [10][11][12][13][14][15][16][17][18] A most important advantage is that the QD can be dispersed in the water by functionalizing the surface. 19,20 Simple but useful fluorescent sensors based on QDs in previous studies monitored changes in the pH through single peak emission changes that occurred by a photoinduced electron transfer (PET) mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…that the particles have to be conjugated with. Despite their relatively large size, recent life science experiments have shown that bioconjugated QD probes behave like fluorescent proteins and do not suffer from serious binding kinetic or steric hindrance problems and can be used in fluorescent imaging of molecular and cellular targets [8,9,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In this ''mesoscopic'' size range, QDs also have a greater surface area and a lot of functionalities to develop multifunctional nanoparticles that can be used for linking to multiple diagnostic and therapeutic agents.…”
Section: Basic Principles Of Design and Synthesis Of Quantum Dotsmentioning
confidence: 99%
“…In contrast, using small QDs (approximately 2-3 nm in diameter) it is possible to obtain nanobiohybrids that consist of several QD particles attached to a single biomolecule (usually protein) [26]. In this case, QDs have an important privilege for fluorescence detection methods in comparison with classical organic dyesthe attachment of several small size QDs on the surface of one protein molecule does not result in fluorescence self-quenching, in contrast to classical dyes (e.g., cyanines, fluorescein, etc.)…”
Section: Structure Of Quantum Dot Nanobiohybrids For Fluorescent Micrmentioning
confidence: 99%
“…14 QD-based western blotting protocols were useful for the ultrasensitive detection of "tracer" proteins in cell lysates, 23 QD-conjugated hybridization probes were effective for a rapid procedure for the selection of highly effective smallinterfering RNA (siRNA) sequences for RNA interference in mammalian cells, 24 QD-lectin conjugates could identify leukaemia cells from normal lymphocytes using fluorescent confocal microscopy and flow cytometry, 25 QDs could be transfected into the cytoplasm and even the nucleus of the cells using insect neuropeptide, namely, allatostatin 1 from Drosophila melanogaster. 26 The conventional luminescence probe only shows monotonous luminescence changes upon biosensing and causes limited resolution.…”
mentioning
confidence: 99%